PENGEMBANGAN KURIKULUM MATEMATIKA BERBASIS TEORI BELAJAR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMK NEGERI 2 PADANGSIDIMPUAN - Palwina Machrani; Fadilla Sri Utami Siregar; Mariam Nasution (Universitas Islam Sumatera Utara, 2026)
This study aims to develop a mathematics curriculum based on learning theories to improve students' critical thinking skills at SMK Negeri 2 Padangsidimpuan. The method used was Research and Development consisting of needs analysis, design, development, implementation, and evaluation stages. The subjects were tenth-grade students. The instruments included a critical thinking test, observation sheets, and student response questionnaires. The results showed that the developed curriculum met the criteria of validity, practicality, and effectiveness. This was indicated by an increase in the average critical thinking score from 58.8 to 78.9. In addition, the implementation of learning was categorized as very good (86.7%), and student responses were positive (84%). Therefore, the developed curriculum is effective in improving students' critical thinking skills and the quality of mathematics learning.